Respuesta :
This is an arithmetic sequence with a common difference of -9, so the next term will be 35-9=26.
If you examine your sequence closely, you can notice that the number in the tens place is decreasing by 1 as the number in the ones place is increasing by 1.
To further prove this;
71 --> 62.
-10 and + 1.
62 --> 53.
-10 and +1
and so on.
However, if that's a little too complicated, there's an alternate method.
All you have to do is subtract 9 from the current number.
To further prove this;
71 - 9 = 62
62 - 9 = 53
53 - 9 = 44
and so on.
So, let's subtract 9 from our most current number, 35.
35 - 9 = 26.
The upcoming number in your sequence is 26.
I hope this helps!
To further prove this;
71 --> 62.
-10 and + 1.
62 --> 53.
-10 and +1
and so on.
However, if that's a little too complicated, there's an alternate method.
All you have to do is subtract 9 from the current number.
To further prove this;
71 - 9 = 62
62 - 9 = 53
53 - 9 = 44
and so on.
So, let's subtract 9 from our most current number, 35.
35 - 9 = 26.
The upcoming number in your sequence is 26.
I hope this helps!